Errors Analysis of the Fourth Year Preparatory Students in Writing English Composition : Analisis Kesalahan Siswa Kelas Persiapan Tahun Keempat dalam Menulis Komposisi Bahasa Inggris - Habeeb, Ammar Abdul Fattah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Error analysis plays a central role in second language acquisition research and supports the identification of learners’ linguistic difficulties in writing. Specific Background Fourth year preparatory students in Tikrit, Iraq, experience noticeable weaknesses in writing English compositions despite formal instruction in grammar and writing skills. Knowledge Gap Limited empirical evidence exists regarding the distribution of grammatical error types and gender differences among Iraqi preparatory EFL learners. Aims This study aims to identify common error types in students’ English compositions, determine possible causes, and examine differences between male and female students. Results The findings reveal that spelling errors represent the highest proportion (43.04%), followed by verb tense (16.66%), subject–verb agreement (12.08%), and capitalization errors (10.62%). A total of 546 errors were recorded, with male students producing a slightly higher proportion of errors than female students. Novelty The study provides a structured classification of errors using a diagnostic test grounded in an established error analysis model within the Iraqi preparatory context. Implications The results support pedagogical adjustments in writing instruction, targeted feedback strategies, and curriculum design to address frequent grammatical and mechanical errors. Keywords: Error Analysis, EFL Writing, Spelling Errors, Grammatical Errors, Iraqi Preparatory Students Key Findings Highlights: Spelling constitutes the largest proportion of recorded deviations in compositions. Verb tense and agreement issues remain persistent grammatical challenges. Gender comparison shows slightly higher error frequency among male learners.